Liturgical Hebrew as Quasilect; Liturgical English as Sociolect - Sarah Grabiner (Religions)
This paper considers a corpus of translations of blessings in bilingual Hebrew–English prayer books from 1940 to the present day, spanning the breadth of religious and sociocultural outlooks. I show how this little-studied body of Jewish text belies the special nature of liturgical language, and how this register of Hebrew–English language combination, so ubiquitous in Jewish communal life, conveys meaning in a particular manner. I explore how liturgical Hebrew constitutes a quasilect in anglophone Jewish communities and how the language of liturgical translation should be considered a special variety of Jewish English. In light of these theoretical frameworks in the fields of Hebrew and Jewish languages, there is much to learn about the linguistic environment of anglophone Jewish communities from the study of the Hebrew and English varieties contained within bilingual prayer books.